Experimental Study and Parameter Optimization of Hybrid Electrical Discharge Machining - Kumar Singh, Nishant; Agrawal, Sandeep; ., Rajvardhan; Singh, Yashvir (International Journal of Engineering and Technology, 2018)
Hard materials cannot be machined effectively by the individual machining process. In order to machine workpiece made from hard and stiff materials effectively a concept of Hybrid machining process (HMP) is originated. The HMP is an integration of two or more machining process to get the advantage of each individual process. HMP is used to machineÂ  This study focuses on evolving a novel process using both oil and gas as dielectrics to analyse the effect on tool wear rate (TWR) and material removal rate (MRR). The flow of compressed gas through eccentric-hole rotating tool improved the debris removal from inter-electrode gap, hence it improve the flushing competence of the machining process. In this experimental investigation, the workpiece material is Al-20% SiC metal matrix composite (MMC) and the electrode material is copper. The experiments were conducted following the Taguchi method of design experiments. The effect of various machining parameters on MRR and TWR has been studied. The optimization of process parameter has also been done. The results of TWR and MRR are analysed using S/N ratio, ANOVA and main effect plots. The experimental results, revels that discharge current, gap voltage and pulse on time significantly affected MRR, and TWR. The experimental inference reveal that provision of compressed air through eccentric hole rotary tool has a positive effect on machinability of electrical discharge machining (EDM) process.Â Â